2021
DOI: 10.1038/s41563-021-00919-2
|View full text |Cite|
|
Sign up to set email alerts
|

Investigating the nature of active forces in tissues reveals how contractile cells can form extensile monolayers

Abstract: Actomyosin machinery endows cells with contractility at a single cell level. However, within a monolayer, cells can be contractile or extensile based on the direction of pushing or pulling forces exerted by their neighbours or on the substrate. It has been shown that a monolayer of fibroblasts behaves as a contractile system while epithelial or neural progentior monolayers behave as an extensile system. Through a combination of cell culture experiments and in silico modeling, we reveal the mechanism behind thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
127
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(151 citation statements)
references
References 74 publications
17
127
1
6
Order By: Relevance
“…contractile in fibroblasts [11] and extensile in epithelial monolayers [10]. Recently it has even been shown that perturbing the adhesion between cells can result in a switch between extensile and contractile behaviours in epithelial cell layers [21]. While the emergence of extensile or contractile behaviour of topological defects has been widely associated to the activity of these systems, here we show that fluctuations can lead to similar patterns of flows around topological defects and result in both extensile and contractile defect behaviour.…”
supporting
confidence: 49%
“…contractile in fibroblasts [11] and extensile in epithelial monolayers [10]. Recently it has even been shown that perturbing the adhesion between cells can result in a switch between extensile and contractile behaviours in epithelial cell layers [21]. While the emergence of extensile or contractile behaviour of topological defects has been widely associated to the activity of these systems, here we show that fluctuations can lead to similar patterns of flows around topological defects and result in both extensile and contractile defect behaviour.…”
supporting
confidence: 49%
“…Detecting orientational order in epithelia [1,2] has been the focus of several recent studies [3][4][5][6]. The task is commonly approached by tracking the longitudinal direction of individual cells by diagonalizing a rank−2 tensor − i.e.…”
mentioning
confidence: 99%
“…An intriguing possibility how JAM-A-generated signaling events influences cell–matrix adhesions and traction force generation during collective cell migration is that JAM-A acts as a sensor of mechanical forces during collective cell migration. Studies with collectives of migrating cells both in vitro and in vivo indicate that collective cell migration requires mechanical coordination between neighboring cells, and that mechanical forces are transmitted through cell–cell contacts from leader cells at the edges of migrating colonies to the follower cells in their center over a long range [ 11 13 , 15 , 67 ], reviewed in [ 68 , 69 ]. Tension on JAM-A applied through trans-homophilic JAM-A interaction activates RhoA in a Ser285 phosphorylation-dependent manner in CHO cells [ 70 ].…”
Section: Discussionmentioning
confidence: 99%